Alterations of host cell ubiquitination machinery by pathogenic bacteria - Alomairi, Jaafar; Bonacci, Thomas; Ghigo, Eric; Soubeyran, Philippe (Frontiers in Cellular and Infection Microbiology, 2015)
Response of immune and non-immune cells to pathogens infections is a very dynamic process. It involves the activation/modulation of many pathways leading to actin remodeling, membrane engulfing, phagocytosis, vesicle trafficking, phagolysosome formation, aiming at the destruction of the intruder. These sophisticated and rapid mechanisms rely on post-translational modifications (PTMs) of key host cells' factors, and bacteria have developed various strategies to manipulate them to favor their survival. Among these important PTMs, ubiquitination has emerged as a major mediator/modulator/regulator of host cells response to infections that pathogens have also learned to use for their own benefit. In this mini-review, we summarize our current knowledge about the normal functions of ubiquitination during host cell infection, and we detail its hijacking by model pathogens to escape clearance and to proliferate.